POLITICAL AND ECONOMIC ASPECTS OF BANKRUPTCY: THE CASE OF CONSORCIO GRUPO DINA, S.A. DE C.V. - Saavedra García, María Luisa (2011)
The aim of this study was to analyze the politics that led to the bankruptcy of DINA in 2000 and try to measure the economic impact of the same, to raise awareness of the impact the policy decisions detriment of the economic sectors that consequently no longer the engine of industrial development in a region. To analyze the political aspect this study was focused on industrial policy aspects of conducting a comparative analysis of the country’s industrial variables and the state of Hidalgo, as well as GDP, foreign investment and the trade balance. To measure the economic impact was considered necessary to make a comparative analysis of the items that make up municipal revenues. This research concludes that have not been able to count in Mexico with an industrial policy capable of promoting growth and attract foreign investments into the industry, bringing to stagnate because the income received by the states, so necessary for development, growth and improving the standard of living of the population. So it may be said based partion the trend of municipal revenue is adverse economic impact because it has not been able to achieve growth in revenue and that this stagnation is generated precisely by the stagnation in the industrial development of the state.